Managerial Work Behavior: An Integration of Results from Two Major Approaches - Whitely, William (Academy of Management Journal, 1985)
This study integrates results from two major approaches to studying managerial work, one focusing on work content, the other on work process. Clusters of managers having similar work behaviors were first identified in terms of each approach, and major differences among the manager clusters were described. The study next found a moderate convergence in the results of the two approaches. Clusters of managers having similar work content in their jobs were often associated with one or two clusters of work process characteristics. However, the differences between the two clusters of process characteristics associated with one content cluster were often very great. The implicating of these findings for the study of managerial work are discussed and future research directions proposed.